Evolution of a valley the Androscoggin story - Jones, Page Helm. (Canaan, N.H. : Phoenix Pub., 1975)
The history of the Androscoggin Valley tracing the changes from before the white man through water pollution and present reclamation efforts.
Includes bibliographical references (p. 167-169) and index.
Keywords: Androscoggin Valley, (Me.) -- History